T. V. McGowan: PECULIARITIES OF PARAGON NAMES TRANSLATION - McGowan, T. V. (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Paragon names are linguistic means which are culturally charged and reflect the system of values of a definite linguo-cultural community because their primary referents are considered to be prototypes, the best examples of certain qualities and/or actions, which allows paragon names to nominate these qualities and, as a result, to be used to characterize other subjects/objects. The set of paragon names is relatively unique for each culture which creates difficulties of their perception and translation by representatives of different linguo-cultural communities. It is important to find ways of paragon names translation which is the task of this article. The singled out types of paragon names, namely, individual, communal, national, and universal ones, demand different ways of their translation. As a result of the research the following translation models are offered: intact preservation of universal paragon names; preservation of universal paragon names with some additional comments in case of their polysemy; substitution of foreign paragon names (individual, communal, national) by corresponding paragon names from the language the text is translated to; omitting of paragon names unknown to a target culture and their substitution by other lexical means which denote the notion/quality a paragon name nominates.